Strategic Digital Campaign to Improve Rural Health Workers Recruitment Process in Indonesia: A Case Study of Pencerah Nusantara Batch VI - Mochammad Fadjar Wibowo; Yenuarizki; Aghnia Jolanda Putri (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2018)
With current geographical disparities, Indonesia’s ratio of general practitioners (GPs) to population is still lower than the WHO-recommended figure. The Center for Indonesia’s Strategic Initiatives (CISDI) initiated Pencerah Nusantara (PN), a team-based young health workers deployment program to rural areas to improve the distribution of human resources for health including GPs, nurses, midwives, public health specialists, and health advocates. Entering PN’s sixth year of implementation, aimed to attract more application from young health workers, particularly of GPs, CISDI employed strategic digital campaign involving strategic content development, strategic content channeling and strategic content promotion; as an intervention to improve the recruitment process of PN Batch 6. This paper investigates whether the intervention manages to improve the recruitment process of PN and mainly using secondary data such as “Relative Volume Search” measuring Google search popularity, social media insights measuring social media engagement and Google Analytics of PN weblog measuring weblog visits and online recruitment data measuring PN daily application rate from 2016 and 2017. Following the intervention, Google search popularity was doubled, social media engagement showed improvement range from 153 percent to 1,813 percent and PN daily application rate increased 148 percent of health workers and 192 percent of GP, compared to 32 percent and 44 percent of 2016 accordingly. A specifically targeted digital campaign implemented substantially improved recruitment promotion indicated by the significant growth of PN daily application rate.